Teaching adolescents with autism : practical strategies for the inclusive classroom - Kaweski, Walter (New York : Skyhorse Publishing, 2014)
Award-winning educator Walter Kaweski offers secondary teachers practical strategies and heartfelt insights based on his extensive experience as an autism specialist, inclusion coordinator, and father of a son with Asperger syndrome. Students with special needs often require extra support as they adjust to middle and high school and the changes that accompany adolescence. Without support, this time can be overwhelming. Teaching Adolescents with Autism offers hundreds of valuable ideas to help teachers: understand the causes and manifestations of autism, solve adolescent behavior challenges, support students with diverse needs, implement academic and behavioral interventions, help students adjust to social situations and understand special education policy. Each chapter offers numerous personal stories that illustrate and reinforce strategies in a tangible way. Important concepts are augmented with bulleted lists, tables, figures, photographs, and cartoons drawn by a student with autism. This unique book takes the mystery out of teaching adolescents with autism and inspires teachers to appreciate the individuality of each student.
1. Understanding autism -- 2. Understanding inclusive education -- 3. Promoting positive behavior -- 4. Communication: building competence -- 5. Friendship and belonging -- 6. Understanding support: successful strategies for supporting diverse learning needs -- 7. Classroom instruction: effective strategies for whole-class instruction -- 8. Organization.
Includes bibliographical references and index.
Keywords: AUTISTIC CHILDREN -- EDUCATION